Rural Finance for the Poor: From Unsustainable Projects to Sustainable Institutions - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2001)
That has to be uppermost in our minds as we think about what microfinance means. For IFAD, the finance issue is crucial to the task of reducing rural poverty. We do not insist on any particular institutional model. The demand for financial services is very diverse even among the poor, and we believe that any sustainable response will have to be pluralistic. Some require access to more capital than local savings systems allow. I am thinking about those who face clear investment opportunities that will allow a sustainable improvement in food security and income. For this sort of effective demand to be met, it is essential that we foster linkages with upstream financial institutions with a much larger capital base. Support can take a wide variety of forms, from intense training of qualifying microfinance institutions, so they may become viable partners with the private sector, to taking equity stakes in private-sector institutions to increase their rural outreach. We have to keep in front of us how the rural poor make their livelihood. If we do that we can begin to chart the concrete means of reducing poverty – and understand the challenges that microfinance and microfinance institutions must confront. – From a presentation by IFAD to a regional microcredit summit, October 2000
Keywords: 330; Ländlicher Finanzmarkt; Informeller Finanzsektor; Mikrofinanzierung; Entwicklungsländer